PROSPECTS OF USING IN RUSSIA OF EXPERIENCE OF CHINA BANKING SYSTEM DEVELOPMENT - L. Ryabchenko (Вестник университета)
The author analyzed the development of China’s banking system from the beginning of economic reforms to the present hasbeen analyzed. The evolution of functions of both the central bank of China and commercial banks has been revealed. It is concluded that the reforms of China’s banking system including its structure were related to the tasks of developing the national economy and the banking system of the state. Direct lending to state enterprises of the «big four» banks allowed to ensure high rates of economic growth, but led to a rapid growth of «bad debts». The recommendations that will allow to increase the volume of lending to Russian development institutions, economic growth has been suggested.